PENGUKURAN DEBIT DAN SEDIMENTASI DAS BATANG LEMBANG BAGIAN TENGAH KENAGARIAN SELAYO KABUPATEN SOLOK - Nisye Frisca Andini (STKIP Pesisir Selatan, 2017)
Research on sediment discharge measurements and DAS rod hollow central part Kenagarian Selayo Solok District, this study was conducted in January 2017- February 2017. This study aims to determine the volume of sediment contained in DAS Batang Lembang central part because a lot of precipitation occurs that causes silting up of the river, the type of research used in this research is descriptive, to achieve the objectives of this study used a survey method. Determination of sample points to take physical condition data on the location of the research is done by using purposive sampling, that the determination of sample points with a certain considerations. The result of the calculation of average river flow in the dry season 3 m3 / sec and average discharge in the rainy season is 68.7 m3 / sec. While the amount of sediment loads (QS) in the dry season is at 24.97651 tons / year and the amount (QS) during the rainy season is 769.1134 tons / year. Based on calculations that have been done can be concluded that the amount of sediment contained in DAS Batang Lembang the middle of the dry season and the rainy season is different, large sedimentation increases with increasing streamflow.